Financing “Green” Projects: Features, Risks and Tools - E. V. Chaikina; V. P. Bauer (Финансы: теория и практика)
The subject of the paper is the “green” projects of companies whose production activities are accompanied by a high level of anthropogenic emissions. The purpose of the paper is to study the features of analysis and practical application of the tools for financing “green” projects (hereinafter referred to as the tools). The relevance of the article is determined by the need to solve the problems of implementing in practice the provisions of Russian legislation on the development of “green” economy in the context of the need to develop and finance “green” projects by members of the National ESG Alliance. The scientific novelty of the paper is to develop the theory of development and practical use of tools, taking into account the peculiarities of their analysis and application. The paper uses theoretical and practical methods to the analysis of scientific publications and simulation results. The research is based on the provisions of normative and legal acts, monographs and scientific works devoted to the analysis, development and financing of “green” projects. Based on the research carried out in the article, the following results were obtained: an analysis was made of the specifics of the requirements for financing “green” projects; clarified the features of the classification of climate risks and formulated an approach to their transformation into corporate credit risks; the composition of the instruments is determined and their interpretation as controlled aggregates is proposed; the operator model of the units was developed, proposals for its practical use were made. The authors recommend that companies with a commodity product range use the operator model and cognitive maps developed on its basis to analyze existing and develop new tools. In the future, “green” companies are encouraged to use the tools obtained on the basis of the operator model and cognitive maps.